Exploring gender as a social construct: re-reading Little Women from a feminist perspective / Atielia Zakaria - Zakaria, Atielia (Faculty of Film, Theatre and Animation, 2015)
This dissertation will examine the novel Little Women (1868), written by Louisa May Alcott in order to explore whether the concept of gender is more of a social construct than a biological reality. My study will focus on analysing the lived experiences of the March sisters, Jo, Amy, Meg and Beth as portrayed by Alcott in the novel. Through my analysis of the March sisters, who are growing up to develop into conventional women against a particular socio-historical context, I will attempt to argue that the motif of gender is dynamic in process and is often bound to perform stereotypically according to certain socio-cultural dictates. My literature review will be divided into three sections. In the initial section I will discuss my theoretical framework in detail. I have selected Mary Wollstonecraft’s A Vindication of the Rights of Woman: with Strictures on Political and Moral Subject (1792), Simone de Beauvoir’s The Second Sex (1949), and the concept of ‘Gender Performativity’, proposed by Judith Butler in Gender Trouble: Feminism and the Subversion of Identity (1990) in order to develop my theoretical framework. In Socio-Historical Framework: The Life and Times of Louisa May Alcott I have focused on the socio-historical context of my primary source. I have discussed Louisa May Alcott’s life and times and her literary outputs, the impacts of the American Civil War on the society in general and on women in particular and the critical receptions of Little Women. My reading and analysis of Little Women will attempt to signal that the concept of gender is mainly developed through certain socio-cultural dictates.